Tourism as a Catalyst for Economic Transformation: A Local Community Empowerment Strategy to Overcome Poverty in the Jember Region - Nazlina Salsabilla; Dewi Puji Lestari; Mokhammad Miftakhul Huda (Takaza Innovatix Labs Ltd., 2026)
Tourism is a vital sector capable of driving economic transformation, particularly in developing regions such as Jember. However, previous studies have largely concentrated on the growth of the tourism industry without thoroughly examining how it empowers local communities or contributes to poverty reduction. This research addresses that gap, as non-inclusive tourism development often results in unequal distribution of benefits for nearby communities. The article aims to outline the key issues surrounding the limited participation and capacity of local residents in tourism activities, while also presenting empowerment strategies that can enhance their overall well-being. This study employs a qualitative method with a case study approach conducted in several tourist villages in Jember Regency. Data were collected through interviews, field observations, and document analysis, then processed using data reduction, thematic categorization, and in-depth interpretation. The findings reveal a collaborative empowerment model involving government actors, local communities, and industry stakeholders that effectively increases income levels and strengthens community self-reliance. The study concludes that inclusive tourism has the potential to act as a catalyst for economic transformation when community-based empowerment strategies are implemented consistently and sustainably.